Decrypting the mechanistic basis of CRISPR/Cas9 protein. (August 2022) - Panda, Gayatri; Ray, Arjun
Abstract: CRISPR/Cas system, a newly but extensively investigated genome-editing method, harbors practical solutions for various genetic problems. It relies on short guide RNAs (gRNAs) to recruit the Cas9 protein, a DNA cleaving enzyme, to its genomic target DNAs. The Cas9 enzyme exhibits some unique properties, like the ability to differentiate self vs. non-self - DNA strands using the base-pairing potential of crRNA, i.e., only CRISPR DNA is entirely complementary to the CRISPR repeat sequences at the crRNA whereas the presence of mismatches in the upstream region of the spacer permit CRISPR interference which is inhibited in case of CRISPR-DNA, allosteric regulation in its domains, and domain reorientation on sgRNA binding. Several groups have contributed their efforts in understanding the functioning of the CRISPR/Cas system, but even then, there is a lot more to explore in this area. The structural and sequence-based understanding of the whole CRISPR-associated bacterial ortholog family landscape is still ambiguous. A better understanding of the underlying energetics of the CRISPR/Cas9 system should reveal critical parameters to design better CRISPR/Cas9s.